Organizational career growth and career commitment: Moderated mediation model of work engagement and role modeling - Son, Su Jin; Kim, Do Yeong (International Journal of Human Resource Management, 2021)
This study aimed to expand our understanding of the role of organizational career growth in relation to career commitment, as mediated by work engagement. In total, 330 respondents recruited from a large hotel and resort company in South Korea were included in the analysis. Structural equation modeling and the PROCESS macro for SPSS were used to analyze the proposed hypotheses. The results revealed that the intrinsic function of organizational career growth was positively associated with work engagement. Furthermore, work engagement mediated the relationship between the intrinsic function of organizational career growth and career commitment. Moreover, employees’ perception of leaders as role models moderated the relationship between work engagement and career commitment. In particular, the mediating role of work engagement in the relationship between the intrinsic function of organizational career growth and career commitment was stronger when employees perceived their leaders as role models. This paper also discusses the theoretical and practical implications of these findings.
Keywords: career commitment; Organizational career growth; role modeling; work engagement